Determinants of public debt in Malaysia/ Fatin Nur Syaffira Abdul Razak - Abdul Razak, Fatin Nur Syaffira (Faculty of Business and Management, 2018)
This research looks at 5 major economic indicators (Gross Domestic Product, Inflation, Interest Rate, Current Account Balance and Foreign Direct Investments) that give impact towards public debt in Malaysia. The study is conducted to investigate the major determinants that influence public debt in a country. The public debt might give the positive or negative impact towards the GDP, inflation rate, interest rate, current account balance an also towards FDI. This relationship will be conducted in Malaysia to shows that whether the result is significant with the previous study. The study is also to show whether Malaysia having the good public debt ranges year to year or vice versa. Moreover, the public debt of the country should be control and the results will lead the country to be better from time to time. The issue of public debt is chosen to compare whether Malaysia having the improvement in GDP, interest rate, inflation, FDI and also with the current account balance. This will prove the overall economic of Malaysia. Indirectly, the study will give the significant result with previous study.